The role of psychological services during the war in Ukraine - Tverdokhliebova, Natalia; Kalinichenko, Viktoria (My University, 2023)
In times of a full-scale invasion of the Ukraine territory by the Russian aggressor, it is necessary to pay attention to the issues of psychological support of the educational process, which is of great importance for ensuring the psychological well-being of students and teachers.
Keywords: psychological services; psychological support; psychological well-being